UKURAN LAYAK TANGKAP DAN DAMPAK EKOLOGIS PENANGKAPAN BARONANG (Siganidae) DI PERAIRAN PULAU HARAPAN, KEPULAUAN SERIBU, JAKARTA - Nur Muhammad Syadli; Am Azbas Taurusman; Prihatin Ika Wahyuningrum; Budy Wiryawan (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
Rabbitfishes (Siganids) fishing activities tend to increase and potentially impact fish target and ecosystem, which is indicated by changes in population size and structure and the trophic level of the catches. Scientific information on Siganids fishing techniques and its ecological impact are limited. The aims of the study are: (1) to describe technical fishing aspects of Siganids fishery; (2) to estimate parameters of length at first maturity (Lm) as catch size limit indicators for this fish target; (3) to evaluate the impact of fishing on food chain balances (trophic level) the fish resources in this study area. The Siganids fishing techniques were observed during the field study. The catch of Siganids species and other fishes from various fishing gears were sampled, then identified and calculated individually. The samples of Siganids fish were also measured for its length and weight. This study showed that the fishers were used three kinds of fishing gears to target the Siganids fish, i.e., rope traps, bamboo traps, and spear gun. There were five species of Siganids caught during the research, they are: Barhead spinefoot (Siganus virgatus), Goldspotted spinefoot (S. punctatus), Streaked spinefoot (S. javus), Orange-spotted spinefoot (S. guttatus), and White-spotted spinefoot (S. canaliculatus), with the Lm value of 3.5, 22.8, 30.6, 21.2, and 20.8 cm, respectively. All catches of the Siganids exceeded the catch size limit (Lm), except for S. punctatus and S. Javus which was only 65.51% and 4.00% of the respective catches were acceptable in size. Finally, the Siganids fishing activities in the study area potentially impacted the ecological function of natural food chain balance (trophic level). It was indicated by the dominance (48%) of the catches on trophic level 3. Keywords: fishing impact, rabbitfish, Siganidae, size limit, trophic level